2002
DOI: 10.1159/000065170
|View full text |Cite
|
Sign up to set email alerts
|

General Practitioners and Predictive Genetic Testing for Late-Onset Diseases in Flanders: What Are Their Opinions and Do They Want to Be Involved?

Abstract: Objective: Investigate the attitudes of general practitioners (GPs) concerning predictive testing for late-onset diseases, as well as the perception of their own role in this context. Methods: 356 GPs received mail questionnaires with telephone pre-notifications and reminders. Results: The questionnaire was returned by 60% (n = 215). The GPs’ attitudes toward predictive testing for breast cancer, thyroid cancer, Alzheimer disease and Huntington’s disease were influenced by the availability and the type of prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
2
16
0
Order By: Relevance
“…35 PCPs also mentioned that genetic testing may have unanticipated findings that are secondary to the intent of ordering testing and that may cause distress among adults and minors regarding adult-onset disorders. 35,36 The second most common ELSI barrier (n = 15 citations in 15/38 studies) was the fear of social or insurance discrimination for their patients as a result of their genetic information. 37 Freedman et al 17 found that more than 80% of 1,251 US PCPs surveyed thought that patients with positive genetic testing results were at risk for insurance discrimination.…”
Section: Genetics In Medicine | Volume 17 | Number 3 | March 2015mentioning
confidence: 99%
See 2 more Smart Citations
“…35 PCPs also mentioned that genetic testing may have unanticipated findings that are secondary to the intent of ordering testing and that may cause distress among adults and minors regarding adult-onset disorders. 35,36 The second most common ELSI barrier (n = 15 citations in 15/38 studies) was the fear of social or insurance discrimination for their patients as a result of their genetic information. 37 Freedman et al 17 found that more than 80% of 1,251 US PCPs surveyed thought that patients with positive genetic testing results were at risk for insurance discrimination.…”
Section: Genetics In Medicine | Volume 17 | Number 3 | March 2015mentioning
confidence: 99%
“…11,15 PCPs also reported being unclear about their role in providing genetics services (n = 15 cited in 15/38 studies). In some instances, PCPs felt that it was not their role to deliver genetics services 8,36,39 or they simply were unclear about their role. 9,12-14,32,37 Additional studies described PCPs' perceptions that "genetics is for specialists" 19,27,29,40 and that the management of genetic conditions requires complex high-level knowledge available only from a specialist.…”
Section: Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the clinical utility of predictive testing has yet to be rigorously evaluated, health providers in all settings need to be informed of genetic issues [1, 2, 3]. Surveys in the United States and other parts of the world indicate that physicians in general practice have limited knowledge of genetics and want only to play a minor role in providing genetic service [4, 5]. In Canada there is emerging evidence that health providers appear willing to expand their roles in providing genetic services [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Parallel efforts are under way to educate physicians, particularly primary care physicians, who are increasingly likely to be involved in counseling patients about AD risk as AD awareness grows and demographic shifts continue. Physicians also have limited knowledge of genetics and weak quantitative skills [44,45,46], plus a limited understanding of the potential risks and benefits of genetic testing [1, 13,46,47,48]. Continued efforts in this area will be critical as medicine moves further into the genomic era.…”
Section: Discussionmentioning
confidence: 99%